Out of the Ivory Tower, into the Digital World? Democratising Scholarly Exchange. Issue 375 (7th February 2022) - Raeburn, Fraser; Baer‐Tsarfati, Lisa; Porter, Viktoria
Abstract: The year 2020 has witnessed an unprecedented expansion of scholarly events online. Yet, in the scramble to adapt to difficult circumstances, little reflection has been given to the ways in which these new digital landscapes can reshape our approach to public history more permanently. This article draws upon the authors' experiences as organisers of the 2020 AskHistorians Digital Conference (AHDC). As one of the first pandemic‐era conferences to be 'born digital', The 2020 AHDC leveraged its online format to challenge the exclusionary nature of traditional academic conferences. By reducing barriers to both participation and access, the event blended scholarly exchange with public engagement on a remarkable scale, reaching a global audience of tens of thousands. In sharing the lessons learned from this undertaking, we argue that digital conferences are not a temporary expediency; rather, they present a revolutionary opportunity not only to reshape the ways in which scholarly conversations take place, but also to reduce artificial divides between academic and public histories.